The emerging double-edged sword role of exosomes in Alzheimer’s disease - Liang, Tao; Wu, Zubo; Li, Junjun; Wu, Suyuan; Shi, Wuhe; Wang, Lin (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD) is the most common neurodegenerative disease characterized by progressive loss of memory and cognitive dysfunction. The primary pathological hallmarks of AD are senile plaques formed by deposition of amyloid β (Aβ) protein, intracellular neurofibrillary tangles resulting from hyperphosphorylation of microtubule-associated protein tau, and loss of neurons. At present, although the exact pathogenesis of AD is still unclear and there is a lack of effective treatment for AD in clinical practice, researchers have never stopped exploring the pathogenic mechanism of AD. In recent years, with the rise of the research of extracellular vesicles (EVs), people gradually realize that EVs also play important roles in neurodegenerative diseases. Exosomes, as a member of the small EVs, are regarded as carriers for information exchange and material transport between cells. Many cells of the central nervous system can release exosomes in both physiological and pathological conditions. Exosomes derived from damaged nerve cells can not only participate in Aβ production and oligomerization, but also disseminate the toxic proteins of Aβ and tau to neighboring neurons, thereby acting as "seeds" to amplify the toxic effects of misfolded proteins. Furthermore, exosomes may also be involved in the degradation and clearance process of Aβ. There is increasing evidence to suggest that exosomes play multiple roles in AD. Just like a double-edged sword, exosomes can participate in AD pathology in a direct or indirect way, causing neuronal loss, and can also participate in alleviating the pathological progression of AD. In this review, we summarize and discuss the current reported research findings on this double-edged role of exosomes in AD.